Mapping the oxidative landscape in cystic fibrosis: methodological frontiers and application - Michela Rubin; Ilaria Artusi; Ilaria Artusi; Giorgio Cozza; Giorgio Cozza (Frontiers in Pharmacology, 2025)
Cystic Fibrosis (CF), a multi-organ disease stemming from CFTR gene mutations, is characterized by progressive pulmonary disease, chronic inflammation, and a pro-oxidative environment. The intricate relationship between CFTR dysfunction, oxidative stress, and inflammation underscores the need to accurately characterize oxidative stress markers to identify therapeutic targets. This review compiles and analyzes methodologies employed in the CF field for this purpose, presenting selected applications and outcomes while highlighting potential inconsistencies due to experimental variations. The review encompasses a wide array of analytical techniques. These include methods for direct reactive oxygen species (ROS) detection (e.g., superoxide, hydrogen peroxide), characterization of oxidative damage to lipids (e.g., TBARS, F2-isoprostanes; lipidomics), proteins (e.g., carbonylation, S-nitrosylation, S-glutathionylation; proteomics), and DNA (e.g., 8-OHdG). Assays for major non-enzymatic antioxidants (glutathione, vitamins), enzymatic antioxidant systems (superoxide dismutase, catalase, glutathione peroxidase), and total antioxidant capacity (TAC) are detailed. Furthermore, methods to assess mitochondrial function for studying oxidative stress in CF are discussed. The critical choice of experimental models (in vitro, in vivo) and biological samples (e.g., blood, sputum, BALF, EBC, cells), along with their specific considerations, are also integral to the review. Application of these diverse methodologies frequently reveals heightened oxidative stress and perturbed antioxidant defenses across various CF-relevant compartments, although results can be influenced by the specific model or technique utilized. Ultimately, this comprehensive analysis underscores the complexity of assessing oxidative stress in CF and strongly advocates for the implementation of integrated, multiparametric strategies. Such synergistic approaches, combining complementary methodologies, are crucial for a holistic understanding of redox dysregulation, facilitating the identification of reliable biomarkers, and guiding the development of more effective, targeted antioxidant therapies to improve clinical outcomes in CF.